Walras' law in the context of pre-analytic visions: A note - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
Walras' law is central to the formation of economic theory. For mainstream economics, it is a device for testing rigorousness and consistency of model-building; for heterodox economists, the refutation of Walras' law is key to understanding Keynes' revolutionary contribution to a new economic paradigm. The purpose of this short research note is to elaborate on the possibility of a refutation of Walras' law and to inquire into its preconditions. It will be argued that this can only be achieved on the basis of an alternative pre-analytic vision of a genuine monetary economy as forshadowed by John Maynard Keynes.
Keywords: B50; D50; D51; E12; 330; Walras' law; equilibrium; disequilibrium; heterodoxy; orthodoxy